Use of Herbal Medicines for the Treatment of Mild Mental Disorders and/or Symptoms During Pregnancy: A Cross-Sectional Survey - Gantner, Giulia; Spiess, Deborah; Randecker, Eliane; Quack Lötscher, Katharina C.; Simões-Wüst, Ana Paula (Frontiers in Pharmacology, 2021)
Little is known about the treatment of mild mental disorders and/or symptoms (MDS) during pregnancy. Our main purpose was to compare the use of herbal medicines during pregnancy in women with and without MDS. A questionnaire consisting of 21 multiple-choice questions was distributed in the participating obstetrics clinics or birth centers in the Canton of Zurich, in Switzerland, from August 2018 to March 2019; 398 questionnaires were considered in the analysis. The use of any type of herbal medicines – including pharmaceutical herbal products as well as teas – during pregnancy was reported by 358 women (out of 398, 89.9%). Of these, 272 participants used pharmaceutical herbal products, whereby ginger (49.2%), raspberry leaf (42.7%), bryophyllum (37.8%), chamomile (27.2%), lavender (22%) and iron-rich herbs (12.3%) were the ones most commonly mentioned. More than half (207/398, 52.0%) of all participants reported suffering from MDS during pregnancy; only a few took (synthetic) psychoactive medications (5/398, 1.3%). The percentage of use of pharmaceutical herbal medicines was higher among women reporting MDS than among the remaining women (90.0% vs. 75.9%; p<0.001). At the same time, the prevalence of MDS was higher among users of pharmaceutical herbal products than among non-users (59.6% vs. 34.0%; p=0.001). Specific questions on candidate herbal medicines for the treatment of mild MDS revealed that bryophyllum (mentioned by 107 women), lavender (56 women) and valerian (20 women) were used to reduce stress, restlessness, sleep disorders and others, in part with perceived good to very good effectiveness and tolerability. The large majority of the pregnant women participating in the survey make use of herbal medicines. The particularly high prevalence of MDS among herbal medicine-users and the very rare use of synthetic psychoactive medications suggest that pregnant women rely on herbal medicines for treatment of mild MDS. The reported good effectiveness and tolerability of a few candidate herbal medicines deserve particular attention.